PENGARUH GAJI TERHADAP MOTIVASI KERJA KARYAWAN PADA PT. SICEPAT EKSPRESS CABANG BIMA - Abd. Gafur; Muhammad Yusuf; Firmansyah Kusumayadi (Lembaga Pengembangan Kinerja Dosen, 2022)
This study was conducted with the aim of testing the effect of leverage and firm size on Islamic social The title of the research is the influence of salary on employee work motivation at PT. Sicepat Ekspress Bima Branch. The type of research used in this study is associative. The instrument used in this research is in the form of data collection by using the method of observation, bibliography,and questionnares with a Likert scale. The population used in this study were all employee at PT. Sicepat Ekspress Bima Branch, totalling 30 people. The type of sample used in this study is saturated sampling. The location in this research is JL. Gajah Mada RT.09 RW.03 Penatoi subdistrick, Mpunda Dictrick, Bima City NTB Province with a postal code of 4115. The data analysis technique used SPSS Version 26. The data testing technique used Validity and Reliabilty test,simple linear regression test, correlation coefficient, determination, and T test or significant test.